MANAGER’S COMPETENCIES OF THE DIGITAL REVOLUTION ERA - T. Yu. Krotenko; M. B. Zhernakova (Вестник университета, 2019)
The society is steadily moving towards digitalization. To implement the transformations planned for most sectors of the economy, the well-functioning of the already formulated managerial competencies is required. At the same time, it is difficult to imagine a “step into the future” without additional efforts in this direction. According to the authors, there is an urgent need to develop new “profiles of success” − cross-professional complexes of knowledge and skills, and then – their optimal implementation in the daily activities of specialists. Competencies evolve quickly, therefore, each manager is required additional responsibility-to monitor the effectiveness of their competencies and update them in accordance with the requirements of time.